Building Students' Social Skills in Learning Conflict Resolution in Grade IV of Laboratory Elementary School - Istianti, Tuti; Maftuh, Bunyamin; Maryani, Enok; Wahyuningsih, Yona (PrimaryEdu : Journal of Primary Education, 2023)
This study aims to describe the results of students' social skills in learning conflict resolution in the fourth grade of Laboratory Elementary School of UPI Cibiru Campus. The research method used is qualitative research. Research results show that the implementation of conflict resolution learning in building social skills in grade IV is carried out through three stages, i.e., 1) preparation stage, 2) implementation stage, and 3) evaluation stage. The preparation stage is the stage of conducting curriculum analysis to see graduate competency standards, core competencies, and basic competencies; mapping the competencies, determining themes, compiling materials, designing evaluation tools, and designing lesson plans. The implementation phase consists of: 1) opening activities, 2). the main activities which include the following stages: search, logical reasoning, agreement building, decision making, conflict reflection, and 3) closing activities. The evaluation phase includes the assessment of affective, knowledge, and social skills competence.Learning conflict resolution for the fourth graders of Laboratory Elementary School of UPI Cibiru in Bandung Regency has an impact on the development of students' social skills including thinking skills, cooperation skills, and emotional control skills. Teachers have focused attention on setting up learning systems and developing conflict resolution learning that enables students to increase their social skills.